Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/17455065211017066
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice on screening toward cervical cancer among health professionals in India—A review

Abstract: Background: Globally, 570,000 cases of cervical cancer and 311,000 deaths from the disease occurred in 2018. Cervical cancer is the fourth most common cancer in women. About 96,922 new cervical cancer cases are diagnosed annually in India. Objective: To summarize the knowledge, attitude, and practice toward screening of cervical cancer among health professionals in India. Materials and methods: Health sciences electronic databases PubMed and Google Scholar were searched for studies published between 2012 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(77 reference statements)
0
4
0
3
Order By: Relevance
“…9 A study in over 6000 health care professionals, The knowledge, attitude, and practice toward screening for cervical cancer was 86.20%, 85.47%, and 12.70%, respectively. 10 In a recently published systematic review on observing the practice of screening methods in study participants, 14 out of 15 studies reported that only 27.37% of the women practiced BSE, while practice of CBE and mammography was even lower 16.71% and 7.12% respectively. 11 While the knowledge was good, attitude was correct but practice was still poor.…”
Section: Discussionmentioning
confidence: 99%
“…9 A study in over 6000 health care professionals, The knowledge, attitude, and practice toward screening for cervical cancer was 86.20%, 85.47%, and 12.70%, respectively. 10 In a recently published systematic review on observing the practice of screening methods in study participants, 14 out of 15 studies reported that only 27.37% of the women practiced BSE, while practice of CBE and mammography was even lower 16.71% and 7.12% respectively. 11 While the knowledge was good, attitude was correct but practice was still poor.…”
Section: Discussionmentioning
confidence: 99%
“…En el estudio, los médicos tuvieron un mayor porcentaje de respuestas correctas sobre síntomas del cáncer de cuello uterino, mientras que las preguntas menos correctas fueron sobre identificación de lesiones precancerosas, esto es alarmante porque el enfoque está en la identificación de lesiones precancerosas o sospecha, de forma que se traslade a un hospital donde puedan confirmar o descarta la enfermedad, lo que lleva a un diagnóstico oportuno y tratamiento temprano, previniendo desenlaces fatales (21,27). Otros estudios concuerdan con nuestros resultados y describen que el conocimiento sobre signos y síntomas y factores de riesgo de cáncer de cuello uterino, fue adecuado entre los profesionales de la salud (28)(29)(30). Sin embargo, otros estudios encontraron que el personal de salud tenían escaso conocimiento del cáncer de cuello uterino como enfermedad (31,32) y la formación de los profesionales sanitarios que trabajan en el sector salud para el diagnóstico precoz del cáncer de cuello uterino no son suficientes (33).…”
Section: Discussionunclassified
“…El presente trabajo encontró que las habilidades académicas y diagnósticas son óptimas en la prevención y detección temprana del cáncer de cuello uterino, esto puede deberse que este cáncer es una de las principales causas de muertes en el Perú, existe difusión por medios de comunicación las medidas preventiva para el cáncer de cuello uterino, así mismo con frecuencia se pueden observar a los pacientes en los centros de salud, pero en estados avanzados del cáncer (20,36,37). Nuestro resultado coincide con otros estudios, donde los médicos presentan un nivel adecuado de conocimiento sobre cáncer de cuello uterino, pero un pobre conocimiento sobre las medidas preventivas (28,38,39). Sin embargo otro estudio encontró que los profesionales de la salud tenían un nivel regular sobre la prevención de cáncer de cuello uterino (29,31).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…India is primed for improving cancer care, including and especially for women, for example, given existing capacities of the health workforce. A recent study on cervical cancer screening demonstrated that the knowledge of healthcare professionals regarding symptoms and risk factors is over 75 per cent 24 . This review provides an overview of the value-based healthcare approach, identifies areas for enhancing the objectives of value-based care and proposes health system strategies to improve comprehensive value-based care in India within the current context, focusing on implications for women’s cancers.…”
Section: Introductionmentioning
confidence: 99%